CCL28: A Promising Biomarker for Assessing Salivary Gland Functionality and Maintaining Healthy Oral Environments - Yuichiro Kaibori; Saho Tamoto; Sayoko Okuda; Kazuhiko Matsuo; Takashi Nakayama; Daisuke Nagakubo (Biology, 2024)
The oral cavity serves as the primary path through which substances from the outside world enter our body. Therefore, it functions as a critical component of host defense. Saliva is essential for maintaining a stable oral environment by catching harmful agents, including pathogens, allergens, and chemicals, in the air or food. CCL28, highly expressed in mucosal tissues, such as the colon and salivary glands, is a chemokine that attracts CCR10/CCR3 expressing cells. However, the role of CCL28 in salivary gland formation remains unclear. In this study, we investigated the salivary gland structure in CCL28-deficient mice. Histological analysis showed decreased staining intensity of Alcian blue, which detects acidic mucous, reduced expression of MUC2, and higher infiltration of gram-positive bacteria in the salivary glands of CCL28-deficient mice. In addition, CCL28-deficient mice contained ectopically MUC2-expressed cells in the ducts and reduced the expression of cytokeratin 18, a marker for ductal cells, within the submandibular glands, resulting in decreased duct numbers. Additionally, the submandibular glands of CCL28-deficient mice showed reduced expression of several stem cell markers. These results suggest that CCL28 regulates saliva production via proper differentiation of salivary gland stem cells and could be a valuable biomarker of salivary gland function.